2009
DOI: 10.1109/led.2008.2008665
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Stretchable Multilayer Self-Aligned Interconnects for Flexible Electronics and Large-Area Sensor Arrays Using Excimer Laser Photoablation

Abstract: Stretchable interconnects are fabricated on polymer substrates using metal patterns both as functional interconnect layers and as in situ masks for excimer laser photoablation. Singlelayer and multilayer interconnects of various designs (rectilinear and "meandering") have been fabricated, and certain "meandering" interconnect designs can be stretched up to 50% uniaxially while maintaining good electrical conductivity and structural integrity. This approach eliminates masks and microfabrication processing steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…[53][54][55][56][57][58][59]61,[62][63][64][65][66][67][68][69][70][71][72] This approach, which receives inspiration from Whitesides et al [62] who observed that thin films of Au deposited onto PDMS form wavy, buckled shapes, represents the basis of some of the original work in stretchable electronics. Stretchability derives from the mechanics of such metal structures, which electrically interconnect separately fabricated, rigid active device regions that remain flat and non-stretched.…”
Section: Stretchable Metal Interconnects Between Rigid Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[53][54][55][56][57][58][59]61,[62][63][64][65][66][67][68][69][70][71][72] This approach, which receives inspiration from Whitesides et al [62] who observed that thin films of Au deposited onto PDMS form wavy, buckled shapes, represents the basis of some of the original work in stretchable electronics. Stretchability derives from the mechanics of such metal structures, which electrically interconnect separately fabricated, rigid active device regions that remain flat and non-stretched.…”
Section: Stretchable Metal Interconnects Between Rigid Devicesmentioning
confidence: 99%
“…[67] A different, but related type of stretchable electrode involves S-shaped serpentine patterns of metal lines fabricated on a carrier wafer and then embedded in PDMS by encapsulation and transfer. [55][56][57][58][59]61] Deformations of these initially planar structures occur primarily at the curved edges of the serpentines, to accommodate applied strain (e.g., Fig. 3c).…”
Section: Stretchable Metal Interconnects Between Rigid Devicesmentioning
confidence: 99%
“…Young's moduli and Poisson's ratios for the three layers are E t , E m and E b , and ν t , ν m and ν b , respectively. Due to the fact that the structure for flexible electronics is long and thin ( Jia et al, 2011;Lee and Liu, 2014;Lin and Jain, 2009;Yu et al, 2013 ), the top and bottom layers behave as the slender beams and the model is known as the Euler-Bernoulli beam ( Timoshenko, 1930 ). The soft middle layer is modeled as the shear lag which only accounts for the shear deformation; its validity will be discussed later.…”
Section: Given Slopes Are Imposed At the Ends Of The Hard Layersmentioning
confidence: 99%
“…Recently, many types of interesting approaches have been actively researched and developed. Flexible displays (Gelinck & Leeuw, 2004;Park J. S. et al, 2009), radio-frequency flexible identification tags (Forrest, 2004;Jung M. et al, 2010), flexible and stretchable sensor arrays (Lin K. & Jain, 2009;Someya et al, 2005), flexible electronic circuit systems (Graz & Lacour, 2009;Zschieschang et al, 2010), stretchable lightings (Sekitani et al, 2009a), printable devices (Ishida et al, 2010), and sheet-type communication and power-transmission system (Sekitani et al, 2009b) are the feasible examples. In order to develop the practical systems using these devices, an embeddable nonvolatile memory is strongly required as one of the core devices.…”
Section: Introductionmentioning
confidence: 99%